Knowledge of risk factors and Predisposition to cervical cancer among female undergraduates’ in Oyo state tertiary (2013)
Background: Cervical cancer is one of the conditions that lead to mortality among females. Major risk factors are early sexual debut and multiple sexual partners. Objective: This study investigated the knowledge of risk factors and predisposition to cervical cancer among female undergraduates in University of Ibadan and the Polytechnic, Ibadan, Nigeria. Methods: This descriptive survey was carried out among 346 female students selected using a multi-stage and stratified random sampling technique. Data were collected using a structured questionnaire. Data were analysed using Statistical Package for the social sciences and were presented as frequencies and percentages. Results: Findings revealed that the mean age of respondents was 18.7±7.3 years, 32.7% had ever had sexual intercourse, mainly between ages 17 and 21 years. Majority, 60.4% had high level of knowledge and their perception was good. Participants believed that multiple sex partners predispose an individual to the risk of cervical cancer but many did not understand the implications of early exposure to sexual intercourse. Only, 2.3% of the respondents had been screened for cervical cancer. Conclusion: Efforts should be made to enhance awareness of risk factors and provide accessible screening services.